Pembelajaran Sains berbantuan Augmented Reality di Sekolah: Kajian Literatur Implementasi dan Dampak Bagi Siswa - Mona Anju Sansena; Aqilatun Ni'mah; Hendro Perta; Thoriq; Agus Wildan (Jurnal Pendidikan UNIGA, 2025)
This study aims to examine the implementation and impact of using Augmented Reality (AR) in science learning at schools through a literature review approach. The method used is a descriptive-analytical literature review of scientific publications from 2015 to 2025 that discuss the integration of AR in science education at primary and secondary levels. The findings indicate that the implementation of AR enables the visualization of abstract concepts in a more interactive and contextual manner, and strengthens the constructivist approach to learning. The positive impacts of AR on students are evident in improved conceptual understanding, increased learning motivation, and the development of 21st-century skills. Nevertheless, the use of AR requires adequate infrastructure, teacher competence, and well-planned instructional design to ensure its effective and sustainable application.